Transnational marriage: Thai migrants and foreigners - Saisanguan, Sutin (Thai Journal of East Asian Studies, 2012)
A transnational marriage, or an international marriage, is a marriage between two people from different countries. It is a by-product of the movement and migration of people. Currently, there are around 300,000 Thai women emigrants married to foreign men. Its trend is increased. The objectives of this study were to investigate demographic variables and socio-economic status of transnational marriage Thai migrants (TMTMs); and to examine the impact of cross-cultural marriage on the migrants, community and society as a whole. Research methodology was qualitative method. Both documentary and structured & in-depth interview 5 case studies were employed. Descriptive analysis was performed. Findings were (1) the majority of these TMTMs were women, adulthood, had primary schooling, previously married Thai men but divorced them; had a child prior married to their foreign husbands who paid them a monthly income, and, an economic stability and a quality of life concerned were common reasons why they got the marriage; however, the minority of these women were single, well educated, met their spouse at work or closed relations and have their own income; and also, (2) TMTMs’ quality of life and high income due to the marriage create the social bonds of reciprocity. The 5 case studies reveal the same pattern as literature reviewed. Societies are now face with intensifying debates on the pros and cons of transnational marriage, however. The finding suggested that not only the TMTMs but also population at risk should be accessed needed information and tangible measures to improve QOL. To exchange information among governments, NGOs, the media, and UN agencies was a key factor. Both research and investigative journalism can contribute to improve governance.